2016
DOI: 10.1007/s12161-016-0609-0
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Quantification of GM Maize Using Ready-To-Use RTi-PCR Plates

Abstract: European Union (EU) legislation foresees that food and feed are labelled for their genetically modified organism (GMO) content when the ingredients contain authorised GMOs in a proportion higher than 0.9 %. Non-authorised GMOs are not allowed on the EU market. Exception is made for feed materials containing traces of GM events lawfully placed on the market in non-EU countries and for which an authorisation is pending in the EU or expired: in these cases, a minimum required performance limit (MRPL) of 0.1 % is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They described a ready-to-use system using PSP containing lyophilized primers and probes that reduce laboratory handling steps to a minimum. The same group tried to develop a semi-quantification assay for GM maize using a ready-to-use RTi–PCR plate which allows the qualitative detection of GM event in one single real-time PCR experiment [ 15 ]. For the detection of unapproved GMOs in Japan, Mano et al [ 16 ] suggested a real-time PCR array as a universal platform.…”
Section: Introductionmentioning
confidence: 99%
“…They described a ready-to-use system using PSP containing lyophilized primers and probes that reduce laboratory handling steps to a minimum. The same group tried to develop a semi-quantification assay for GM maize using a ready-to-use RTi–PCR plate which allows the qualitative detection of GM event in one single real-time PCR experiment [ 15 ]. For the detection of unapproved GMOs in Japan, Mano et al [ 16 ] suggested a real-time PCR array as a universal platform.…”
Section: Introductionmentioning
confidence: 99%